An Integrated Assessment of China¿s Ecological Restoration Programs 2009
DOI: 10.1007/978-90-481-2655-2_9
|View full text |Cite
|
Sign up to set email alerts
|

Conservation Payments, Liquidity Constraints and Off-Farm Labor: Impact of the Grain for Green Program on Rural Households in China

Abstract: This study evaluates the labor response of rural households participating in the Grain for Green program in China, the largest payments for ecosystem services program in the developing world. Using a panel data set that we designed and implemented, we find that the participating households are increasingly shifting their labor endowment from on-farm work to the off-farm labor market. However, the effects vary depending on the initial level of human and physical capital. The results support the view that one re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
119
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(130 citation statements)
references
References 31 publications
8
119
1
2
Order By: Relevance
“…Whereas some studies in other areas (Daniels et al, 2010;Uchida et al, 2009) have discussed environmental and socioeconomic effects of PES programs, they are mostly scattered, fragmented, short term and opportunistic . In the reserve, although this study captured some short-term effects, many consequences are neither well-understood nor seriously tackled during the decision making processes.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas some studies in other areas (Daniels et al, 2010;Uchida et al, 2009) have discussed environmental and socioeconomic effects of PES programs, they are mostly scattered, fragmented, short term and opportunistic . In the reserve, although this study captured some short-term effects, many consequences are neither well-understood nor seriously tackled during the decision making processes.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…While several studies (Chen et al, 2009(Chen et al, , 2010Uchida et al, 2009Uchida et al, , 2005Viña et al, 2013;Xu et al, 2002Xu et al, , 2004 have evaluated the effectiveness and efficiency of the GTGP, relatively few (Xu et al, 2002;Yin, 2009) have studied the effectiveness and efficiency of the NFCP. In addition, to our knowledge no study has evaluated the decentralized implementation of the NFCP (e.g., participation of local households) and its environmental and socioeconomic consequences.…”
Section: Introductionmentioning
confidence: 99%
“…However, the GTGP may have exerted an indirect effect on the forest cover dynamics observed during the 2001-2007 period. For example, the GTGP program has been associated with an increase in rural-urban labor migration (Uchida et al 2009), which might reduce human pressure on forests, enabling natural regeneration of disused cropland.…”
Section: Influence Of Conservation Policies On Forest Cover Dynamicsmentioning
confidence: 99%
“…Since budgets are always limited, it would be better that the policy focus on degraded cropland, particularly in desertified regions, and poor households at certain levels of degradation and poverty. Earlier research has therefore indicated that the cost-effectiveness of the policy in terms of environmental benefits and poverty alleviation should be considered on the basis of social and ecological heterogeneity, in order to make it more effective and to achieve its overall goals (Wang et al 2007a, b;Uchida et al 2009;Chen et al 2010;Gauvin et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Related to the abovementioned multiple aims of the SLCP, researchers have indicated a need to assess a potential effect of the policy that the government expects: inducing shifts in economic structure, especially from an agricultural to a non-agricultural economy, to reduce economic instability resulting from the overuse of vulnerable natural resources (Uchida et al 2009;Li et al 2011), and thereby, to reduce future environmental degradation. H-E system perspectives are essential for clarifying these SLCP's long-term social-ecological impacts.…”
Section: Introductionmentioning
confidence: 99%